Solar battery plate - XU JIE; ZHU MINJIE; XIA ZHENGYUE; XING GUOQIANG; LU GANG; YAN XINCHUN (2018)
The utility model provides a solar battery plate, it includes the silicon chip and sets up the electrode on the silicon chip. Electrode package draw together set up in the first main grid line of thefirst face of silicon chip, with a plurality of first thin grid line of first main grid line connection, set up in the dihedral a plurality of second main grid line of silicon chip and with the thin grid line of a plurality of seconds of second main grid line connection. The array orientation of first main grid line is unanimous with the array orientation of second main grid line, and just the twoquantity is the same. Same apart from the homogeneous phase with between the adjacent second main grid line between every adjacent first main grid line, and array orientation is last, the setting ofstaggering each other of first main grid line and second main grid line, first thin grid line and the thin grid line of second are respectively certainly first main grid line and second main grid linedepartment extend, and exte